Analysis of Factors Influencing the Use of Implantable Family Contraceptive Methods - Krismiyati, Murti; Wulandari, Amri; Prihastuti, Mizan (Global Health Science Group, 2024)
Implants are one of the effective and efficient long-term hormonal contraceptives, but the use of implanted contraceptives is still relatively low compared to other contraceptives. The coverage of active family planning participants in 2020 who use the implantable contraceptive method is 8.5%. This figure is much lower when compared to the injectable contraceptive method of 72.9%, the pill method of 19.4%, and the IUD method of 8.5%. If you look at the effectiveness, injections and pills, including short-term contraceptive methods that have a lower level of effectiveness, are compared to the Long-Term Contraceptive Method (MKJP), one of which is implants. The method used in this study is analytical descriptive research with a cross sectional approach. The sample in this study is family planning acceptors at PMB Umi M and PMB Siti Aminah. The research was conducted from October 2, 2024 to October 31, 2024 with a sample of 75 respondents. The data was processed using SPSS version 25 and analyzed using the chi square test. The results of univariate analysis showed that there were more respondents who used implanted birth control, namely 55 respondents (73.3%) compared to those who did not use implanted birth control 20 respondents (26.7%). The results of the chi square statistical test showed that there was a relationship between age and the use of the p value implant contraceptive method (0.000), there was a relationship between education and the use of the p value implant contraceptive method (0.023), there was no relationship between parity and the use of the p value implant contraceptive method (0.561) and there was a relationship between income and the use of the p value implant contraceptive method (0.010). There was a relationship between age and the use of implantable contraceptive methods in PMB in the Kulon Progo area as seen from the p value of 0.000. There is a relationship between education and the use of implantable contraceptive methods in PMB in the Kulon Progo area as seen from the p value of 0.023. There was no relationship between parity and the use of implantable contraceptive methods in PMB in the Kulon Progo area as seen from the p value of 0.561. There is a relationship between income and the use of implantable contraceptive methods in PMB in the Kulon Progo area as seen from the p value of 0.010.